Steady and unsteady flow of non-newtonian fluid in curved pipe with triangular - Baghdad Science Journal (مجلة بغداد للعلوم)
This paper deals with numerical study of the flow of stable and fluid Allamstqr Aniotina in an area surrounded by a right-angled triangle has touched particularly valuable secondary flow cross section resulting from the pressure gradient In the first case was analyzed stable flow where he found that the equations of motion that describe the movement of the fluid